Sensors, Circuits and Instrumentation Systems - Derbel, Faouzi; Derbel, Nabil; Kanoun, Olfa (Advances in systems, signals and devices, 2019)
THE SERIES: ADVANCES IN SYSTEMS, SIGNALS AND DEVICES Systems, Signals & Devices is one of the large specializations in electrical engineering, mechanical engineering and computer sciences. It derives input from physics, mathematics and is an indispensable feature of all natural- and life sciences in research and in application. The new series "Advances in Systems, Signals and Devices" presents original publications mainly from speakers on the International Multi-Conference on Systems, Signal and Devices but also from other international authors. The Conference is a forum for researchers and specialists in different fi elds covering all types of sensors and measurement systems